STUDI KASUS PROSEDUR PEMERIKSAAN FISTULOGRAPHY DENGAN KLINIS FISTULA PERIANAL DI INSTALASI RADIOLOGI RSUD BANYUMAS - Istiparni Istiparni; Fisnandya Meita Astari; Muhamad Fa'ik (JHN: Journal of Health and Nursing, 2026)
A perianal fistula is an abnormal tract connecting the anal canal to the skin surrounding the anus. Fistulography is used to visualize the fistula tract, thereby aiding in diagnosis. At the Radiology Department of Banyumas Regional General Hospital (RSUD Banyumas), the procedure differs from standard theory; specifically, PA and lateral projections are used, no markers are placed on the preliminary image, and undiluted iodine-based contrast media is utilized. This study aims to examine the fistulography procedure for perianal fistula cases at RSUD Banyumas, including the rationale for the chosen projections, the omission of markers, and the use of undiluted contrast media. A descriptive qualitative method with a case study approach was employed from December 2025 to May 2026. Data collection involved observation, interviews, documentation review, and a literature study. Research subjects included three radiographers, one radiologist, one referring physician, and one radiology nurse. Data were analyzed narratively and compared against established theory. The study found that fistulography for perianal fistula at RSUD Banyumas is performed without special patient preparation. Equipment and materials included a DR X-ray unit, apron, 50 cc syringe, Abocath catheter, gloves, gauze, Betadine, and Hexiol (300 mgI/mL) iodine contrast medium (50 cc). The contrast medium is administered incrementally through the Abocath catheter. The examination involves a plain pelvic radiograph (PA projection) followed by post-contrast images in both PA and lateral projections. These projections were selected to visualize the fistula's tract and depth, with the PA projection serving to minimize radiation exposure to the gonads. Markers are not used because the fistula's location is identified via the placement of the Abocath catheter. Using undiluted contrast medium provides higher opacity, ensuring the fistula tract is clearly visualized.